Development of microwave sensing system to measure the sweetness and ripeness of pineapple [electronic resource] - Suhail Najm Abdullah, 1991- author; Mazlina Esa; Fakulti Kejuruteraan Elektrik (2015)
Thesis (Sarjana Kejuruteraan (Elektrik - Elektronik dan Telekomunikasi)) - Universiti Teknologi Malaysia, 2015